Utility of two methodologies in the clinical assessment of oral dryness in postmenopausal women - Rachita Kodandera Chengappa; Veena S Narayanan; Asim M Khan; Mangala P Rakaraddi; Kavitha A Puttaswamy; Jaishankar H Puttabuddi (Wolters Kluwer Medknow Publications, 2016)
Objective: The aim of this study was to assess the oral dryness in postmenopausal women and to correlate the salivary flow rate determined by sialometry with the clinical oral dryness score (CODS) obtained from Challacombe Scale. To correlate between subjective and objective oral dryness and relationship of salivary flow rate with that of the duration of menopause. Materials and Methods: Sixty postmenopausal women were questioned regarding their oral dryness status and the duration of menopause. Patients complaining of xerostomia formed the case group and rest formed the control group. CODS was assessed based on the 10 features of oral dryness. Unstimulated whole salivary (UWS) flow rate was assessed by sialometry for 5 min. Results: Highly significant negative correlation was observed between UWS and CODS (r = −0.651), low negative correlation was noted between the duration of menopause and UWS flow rates (r = −0.159), and no significant correlation was found between subjective oral dryness with that of UWS flow rates (P = 0.0964). There was no statistically significant difference between case and control group with regard to CODS (P = 0.525). Conclusion: A good correlation of CODS with sialometry scores indicates that CODS can be utilized for semiquantitative assessment of oral dryness. It appears that UWS has poor correlation with duration of menopause. Xerostomia and UWS were not significantly related.